Artefacts and their distribution (Scottish Historical and Archaeological Internet Reports, 2009)
The medieval pottery assemblage was concentrated mainly on the High Street and comprised mostly Scottish White gritty ware. Two medieval roof tiles and a small quantity of early post-medieval sherds were also recovered.